2021
DOI: 10.33312/ijar.515
|View full text |Cite
|
Sign up to set email alerts
|

Management Control Systems, Organizational Culture and Village Credit Institution Financial Performance

Abstract: This study aims to provide empirical evidence about the influence of misfit management control systems (levers of control) with an organizational culture that will negatively affect the financial performance of Village Credit Institution (LPD). This study uses a survey method (questionnaire) based on a sample of 149 LPD units in Buleleng Regency with purposive sampling criteria. The research respondents were all three LPD officers (penyarik, pemucuk, and petengen) and one staff each from the credit and account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…This indicates that LPD in Bali did not understand each of the questions asked, thereby influencing the negative results observed. The findings contradict the research by Adiputra and Sujana (2021) which found that a culture with levers of control could influence financial performance.…”
Section: The Impact Of Levers Of Control On Organizational Performanc...contrasting
confidence: 99%
See 1 more Smart Citation
“…This indicates that LPD in Bali did not understand each of the questions asked, thereby influencing the negative results observed. The findings contradict the research by Adiputra and Sujana (2021) which found that a culture with levers of control could influence financial performance.…”
Section: The Impact Of Levers Of Control On Organizational Performanc...contrasting
confidence: 99%
“…The vitality of LPD depends heavily on internal organizational factors in financial and human resources management. Significantly, LPD evaluations correlate with statements on general and risk planning in management control systems, requiring thorough exploration to understand internal errors within the organization (Adiputra & Sujana, 2021). The health of LPD is significantly influenced by internal organizational issues when it comes to financial management and human resources.…”
Section: Introductionmentioning
confidence: 99%
“…Organizational culture has characteristics to understand the existence of an organization's culture. Several characteristics of organizational culture, namely: Individual initiative, namely the level of responsibility for freedom and dependence that individuals have (Adiputra & Sujana, 2021;Choi & Chandler, 2020;Thelen & Formanchuk, 2022). 2) Risk tolerance, which is how far the risk is allowed or may be borne by members.…”
Section: Discussionmentioning
confidence: 99%
“…The Village Credit Institution (LPD) is one of the policies of the Bali Regional Government in an effort to channel capital assistance to rural communities in Bali to improve the village economy. The main activity of the LPD is to collect public funds in the form of savings and deposits, and channel them back to people in need and in the form of loans or credit (Adiputra & Sujana, 2021;Suputra & Hendrayanti, 2021). LPD is a name for a savings and loan business owned by traditional village communities located in the Province of Bali and is a means of rural people's economy (Jayanthi et al, 2021;Sanjaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The LPD's largest income comes from lending, and every credit given cannot be separated from various risks that can threaten the health of the LPD (Adiputra & Sujana, 2021;Saerang et al, 2014). Non-Performing Loan (NPL) is a measure of credit risk which is a parameter of the LPD's soundness level.…”
Section: Introductionmentioning
confidence: 99%